(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The determination of the optimal portfolio has a lot of concern from 1950s until now, therefore the researches introduce many techniques for delineating the optimal portfolio. In this paper we try to use one of these techniques to determine an optimal portfolio using a real world data from al-Saudi exchange, which is the cut-off rate. The issue of this study is how we can select the security to be incorporated in the portfolio, and how many securities should be in it and then what are the fractions or the weights of any securities in the optimal portfolio.